Altered ENaC Is Associated With Aortic Baroreceptor Dysfunction in Chronic Heart Failure - Li, Yu-Long (Am J Hypertens, 2016)
BACKGROUND: Abnormal baroreceptor function contributes to attenuated arterial baroreflex sensitivity in chronic heart failure (CHF). As a mechanosensor in mammalian nonepithelium, the epithelial sodium channel (ENaC) is an amiloride-sensitive and voltage-independent ion channel. The ENaC is thought to be a component of baroreceptor mechanosensitive ion channels in aortic baroreceptor cell bodies and nerve terminals. In this study, therefore, we measured the expression and activation of the ENaC in nodose neuronal cell bodies and aortic baroreceptor nerve terminals in sham and CHF rats. METHODS AND RESULTS: CHF was induced by surgical ligation of left coronary artery. The development of CHF was confirmed by hemodynamic and morphological characteristics. The aortic baroreceptor sensitivity was blunted in anesthetized CHF rats, compared with that in sham rats. The data from immunostaining and western blot analysis showed that the protein of β- and γ-ENaC subunits was expressed in nodose neuronal cell bodies and aortic baroreceptor nerve terminals, whereas the protein of α-ENaC subunit was undetectable. CHF reduced protein expression of β- and γ-ENaC subunits in nodose neuronal cell bodies and aortic baroreceptor nerve terminals. Additionally, the data recorded by the whole cell patch-clamp technique demonstrated that ENaC currents in aortic baroreceptor neurons were lower in CHF rats than that in sham rats. CONCLUSION: These results suggest that reduced protein expression of the ENaC decreases the ENaC activation, which could be involved in attenuation of the aortic baroreceptor sensitivity in the CHF state. Baroreceptors should be a potential therapeutic target for reducing mortality in CHF.